Demographic transition and modern geodemographic processes - Яворська, Вікторія; Калетинська, Альона (Human Geography Journal, 2016)
The article deals with current geodemographic processes in Ukraine as a whole, and in the Ukrainian Black Sea region. The problems of the demographic transition. Analyzed the main geodemographic indicators, modern geodemographic polіcy in Ukraine, geodemographic development processes. The rates of total fertility rate in sub-Ukrainian Black Sea region, which is in demographic research is considered the most valid marker for fertility activity of the population. The conclusions about the demographic prospects of the region.